PENERAPAN CLASSROOM-BASED ASSESMENT (CBA) SEBAGAI UPAYA MENINGKATKAN KOMPETENSI SISWA DI SEKOLAH DASAR - Qoyimah, Durotul; Suwadi, Suwadi (STKIP Persada Khatulistiwa Sintang, 2026)
This study examined the implementation of Classroom-Based Assessment (CBA) at Madrasah Ibtidaiyah Miftahul Ulum Toto Mulyo, focusing on three assessment dimensions: assessment as learning, assessment for learning, and assessment of learning, and their relation to students’ competencies (cognitive, affective, psychomotor, and 21st-century skills/4C). Using a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and document analysis (rubrics, instruments, and learning outcomes). Data analysis followed an interactive process involving data reduction, data display, and source triangulation to ensure credibility. The findings indicate that teachers have integrated several CBA principles into instructional practices, particularly in formative assessment (assessment for learning), which is evident in regular understanding checks and feedback provision. However, the implementation of assessment as learning remains limited due to a lack of structured reflection and self-assessment practices. Assessment of learning is conducted but is not yet fully standardized or transparent to students. In terms of competencies, assessment tends to emphasize cognitive and psychomotor domains, especially in religious practices, while the development of 4C skills (critical thinking, creativity, collaboration, communication) and consistent affective assessment still require improvement. The study recommends enhancing transparency in assessment criteria, developing clear rubrics, strengthening self-assessment practices, and providing teacher training on fair and learning-oriented CBA design and implementation.